'Art and Objecthood', Philosophy. (April 2017) - Melville, Stephen
This article explores the relations between philosophy, criticism and art history in the work of Arthur Danto, on the one hand, and Stanley Cavell and Michael Fried on the other, arguing that in the 50 years since the publication of 'Art and Objecthood', that essay's terms of argument and expression have become increasingly hard to make out.